2022
DOI: 10.1155/2022/4851044
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Prediabetes and Associated Risk Factors in Urban Areas of Pontianak, Indonesia: A Cross-Sectional Study

Abstract: Uncontrolled prediabetes can develop into Type 2 Diabetes mellitus (T2DM). The incidence of T2DM among adults in Pontianak, Indonesia was reported remarkably high. Therefore, this study aimed to investigate the risk factors for prediabetes in adults living in urban areas of Pontianak, Indonesia. A cross-sectional study was conducted in 5 subdistricts of Pontianak. A total of 506 adults underwent screening to obtain subjects with fasting blood glucose (FBS) of ≤124 mg/dL and aged >30 years. Blood pressure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
1
0
0
1
Order By: Relevance
“…Gender in the Czech study was not significant, while it showed a statistically significant effect on prediabetes in the German study. Our analysis also found that hypertension has a statistically significant effect on prediabetes, which has been shown in many studies (9,40,44,47). All of the aforementioned risk factors, except waist circumference, are considered general risk factors for cardiovascular diseases and are included as such in numerous cardiovascular risk calculators.…”
Section: Discussionsupporting
confidence: 79%
“…Gender in the Czech study was not significant, while it showed a statistically significant effect on prediabetes in the German study. Our analysis also found that hypertension has a statistically significant effect on prediabetes, which has been shown in many studies (9,40,44,47). All of the aforementioned risk factors, except waist circumference, are considered general risk factors for cardiovascular diseases and are included as such in numerous cardiovascular risk calculators.…”
Section: Discussionsupporting
confidence: 79%
“…Kegiatan pencegahan itu meliputi skrining gula darah dan pemeriksaan fisik. 18 Sementara IMT seseorang memiliki hubungan yang sangat signifikan dengan risiko pradiabetes. Orang dengan berat badan lebih dan obesitas memiliki risiko pradiabetes lebih besar.…”
Section: Pembahasanunclassified